Pragmatic Randomized Trials Without Standard Informed Consent?: A National Survey - Nayak, Rahul K (Ann Intern Med, 2015)
BACKGROUND: There is significant debate over whether written consent is necessary for low-risk, pragmatic randomized controlled trials (RCT). OBJECTIVE: To assess the U.S. public’s views regarding alternatives to written consent for low-risk pragmatic RCTs. DESIGN: National experimental survey (2-by-2 factorial design) examining support for written consent versus general notification or verbal consent in two research scenarios. SETTING: Web-based survey conducted in December 2014. PARTICIPANTS: 2130 U.S. adults sampled from a nationally representative probability-based online panel (response rate, 64%). MEASUREMENTS: Respondent’s recommendation to an ethics review board and personal preference as a potential participant for how to obtain consent/notification in the two research scenarios. RESULTS: A majority in each of the four arms (ranging from 60.3% to 71.5%) recommended written informed consent. Personal preferences generally tracked that advice. Most (78.9%) believed the pragmatic RCTs did not pose additional risks but 62.5% of these respondents would still recommend written consent. In contrast, a substantial minority in all arms (28.5% to 39.7%) recommended the alternative option (general notification or verbal consent) over written consent. LIMITATIONS: Framing effects could impact respondents’ attitudes and non-respondents may differ in levels of trust towards research or healthcare institutions. CONCLUSIONS: A majority of the public endorsed written informed consent over the most widely considered alternatives for low-risk pragmatic RCTs; however, a substantial minority endorsed general notification or verbal consent. PRIMARY FUNDING SOURCE: Time-sharing Experiments in the Social Sciences and Intramural Research Program of the National Institutes of Health, Clinical Center.